Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Impact of climate change on diarrhoea risk in low- and middle-income countries - Syeda H. Fatima; Melinda A. Judge; Peter N. Le Souëf; Corey J.A. Bradshaw (Environmental Research, 2025)

Efficient force calculations in strongly correlated materials within DFT+G using Portobello - Corey Peters; Ran Adler; Garry Goldstein; Yong-Xin Yao; Nicola Lanata; Gabriel Kotliar (Computer Physics Communications, 2025)

Ni isotope cycling in sediments of highly productive upwelling systems - Tim Sweere; Corey Archer; Sarah Fleischmann; Florian Scholz; Peter Kraal; Derek Vance (Earth and Planetary Science Letters, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Correction to: Insular and mainland interconnectivity in the movements of oceanic manta rays (Mobula birostris) off Mexico in the Eastern Tropical Pacific - Robert D. Rubin; Katherine R. Kumli; A. Peter Klimley; Joshua D. Stewart; James T. Ketchum; Edgar M. Hoyos‑Padilla; Felipe Galván‑Magaña; Aldo A. Zavala‑Jiménez; Iliana A. Fonseca‑Ponce; Megan Saunders; P. Santiago Dominguez‑Sanchez; Paul Ahuja; et al. (Environmental Biology of Fishes, 2025)

Insular and mainland interconnectivity in the movements of oceanic manta rays (Mobula birostris) off Mexico in the Eastern Tropical Pacific - Robert D. Rubin; Katherine R. Kumli; A. Peter Klimley; Joshua D. Stewart; James T. Ketchum; Edgar M. Hoyos-Padilla; Felipe Galván-Magaña; Aldo A. Zavala-Jiménez; Iliana A. Fonseca-Ponce; Megan Saunders; P. Santiago Dominguez-Sanchez; Paul Ahuja; et al. (Environmental Biology of Fishes, 2025)

Quantifying geomorphic form variation for assessing habitat complexity of river restoration designs - Corey Dawson; Peter Ashmore (Ecological Engineering, 2025)

Sexually selected differences in warbler plumage are related to a putative inversion on the Z chromosome - Peter O. Dunn; Nicholas D. Sly; Corey R. Freeman‐Gallant; Amberleigh E. Henschen; Christen M. Bossu; Kristen C. Ruegg; Piotr Minias; Linda A. Whittingham (Molecular Ecology, 2024)
Large structural variants in the genome, such as inversions, may play an important role in producing population structure and local adaptation to the environment through suppression of recombination. However, relatively few studies have linked inversions to phenotypic traits that are sexually selected and may play a role in reproductive isolation. Here, we found that geographic differences in the sexually selected plumage of a warbler, the common yellowthroat ( Geothlypis trichas ), are largely due to differences in the Z (sex) chromosome (males are ZZ), which contains at least one putative inversion spanning 40% (31/77 Mb) of its length. The inversions on the Z chromosome vary dramatically east and west of the Appalachian Mountains, which provides evidence of cryptic population structure within the range of the most widespread eastern subspecies ( G. t. trichas ). In an eastern (New York) and western (Wisconsin) population of this subspecies, female prefer different male ornaments; larger black facial masks are preferred in Wisconsin and larger yellow breasts are preferred in New York. The putative inversion also contains genes related to vision, which could influence mating preferences. Thus, structural variants on the Z chromosome are associated with geographic differences in male ornaments and female choice, which may provide a mechanism for maintaining different patterns of sexual selection in spite of gene flow between populations of the same subspecies.

Effects of older age on visual and self-motion sensory cue integration in navigation - Corey S. Shayman; Maggie K. McCracken; Hunter C. Finney; Andoni M. Katsanevas; Peter C. Fino; Jeanine K. Stefanucci; Sarah H. Creem-Regehr (Experimental Brain Research, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

How climate change degrades child health: A systematic review and meta-analysis - Lewis J.Z. Weeda; Corey J.A. Bradshaw; Melinda A. Judge; Chitra M. Saraswati; Peter N. Le Souëf (Science of The Total Environment, 2024)

Sea level rise drowned a vast habitable area of north-western Australia driving long-term cultural change - Kasih Norman; Corey J.A. Bradshaw; Frédérik Saltré; Chris Clarkson; Tim J. Cohen; Peter Hiscock; Tristen Jones; Fabian Boesl (Quaternary Science Reviews, 2024)

Multi-proxy paleohydrological and paleoecological reconstruction of a subaquatic cave in western Cuba - Matthew C. Peros; Shawn Collins; Joao Gabriel Martínez-López; Lázaro W. Viñola López; Miguel Angel Pereira Sosa; Laurence Forget Brisson; François Hardy; Michel Lamothe; Peter J. van Hengstum; Bil Phillips; Kenneth Broad; Jill Heinerth; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Going with the flow: The case of three tropical reef fish transported to cool temperate waters following an extreme marine heatwave - Peter G. Coulson; Tim Leary; Arani Chandrapavan; Corey B. Wakefield; Stephen J. Newman (Regional Studies in Marine Science, 2023)

Fatty acid profiles of more than 470 marine species from the Southern Hemisphere - Peter D. Nichols; Heidi R. Pethybridge; Bowen Zhang; Patti Virtue; Lauren Meyer; Zahirah Dhurmeea; Lara Marcus; Jessica A. Ericson; Nicole Hellessey; Sharon Every; Kathryn Wheatley; Christopher C. Parrish; et al. (Ecology, 2023)
Lipid and fatty acid datasets are commonly used to assess the nutritional composition of organisms, trophic ecology, and ecosystem dynamics. Lipids and their fatty acid constituents are essential nutrients to all forms of life because they contribute to biological processes such as energy flow and metabolism. Assessment of total lipids in tissues of organisms provides information on energy allocation and life‐history strategies and can be an indicator of nutritional condition. The analysis of an organism's fatty acids is a widely used technique for assessing nutrient and energy transfer, and dietary interactions in food webs. Although there have been many published regional studies that assessed lipid and fatty acid compositions, many only report the mean values of the most abundant fatty acids. There are limited individual records available for wider use in intercomparison or macro‐scale studies. This dataset consists of 4856 records of individual and pooled samples of at least 470 different marine consumer species sampled from tropical, temperate, and polar regions around Australia and in the Southern, Indian, and Pacific Oceans from 1989 to 2018. This includes data for a diverse range of taxa (zooplankton, fish, cephalopods, chondrichthyans, and marine mammals), size ranges (0.02 cm to ~13 m), and that cover a broad range of trophic positions (2.0–4.6). When known, we provide a record of species name, date of sampling, sampling location, body size, relative (%) measurements of tissue‐specific total lipid content and abundant fatty acids, and absolute content (mg 100 g −1 tissue) of eicosapentaenoic acid (EPA, 20:5n3) and docosahexaenoic acid (DHA, 22:6n3) as important long‐chain (≥C 20 ) polyunsaturated omega‐3 fatty acids. These records form a solid basis for comparative studies that will facilitate a broad understanding of the spatial and temporal distribution of marine lipids globally. The dataset also provides reference data for future dietary assessments of marine predators and model assessments of potential impacts of climate change on the availability of marine lipids and fatty acids. There are 480 data records within our data file for which the providers have requested that permission for reuse be granted, with the likely condition that they are included as a coauthor on the reporting of the dataset. Records with this condition are indicated by a “yes” under “Conditions_of_data_use” in Data S1: Marineconsumer_FAdata.csv (see Table 2 in Metadata S1 for more details). For all other data records marked as “No” under “Conditions_of_data_use,” there are no copyright restrictions for research and/or teaching purposes. We request that users acknowledge use of the data in publications, research proposals, websites, and other outlets via formal citation of this work and original data sources as applicable.

A data framework for assessing social inequality and equity in multi‐sector social, ecological, infrastructural urban systems: Focus on fine‐spatial scales - Lara P. Clark; Samuel Tabory; Kangkang Tong; Joseph L. Servadio; Kelsey Kappler; Corey Kewei Xu; Abiola S. Lawal; Peter Wiringa; Len Kne; Richard Feiock; Julian D. Marshall; Armistead Russell; et al. (Journal of Industrial Ecology, 2022)
Cities are increasingly advancing multiple societal goals related to environmental sustainability, health, well‐being, and equity. However, there are few comprehensive data sets that address social inequality and equity across multiple infrastructure sectors, determinants, and outcomes, particularly at fine intra‐urban spatial scales. This paper: (1) Offers an overarching conceptualization of inequality and equity in multi‐sector urban systems; (2) Introduces a broad data framework to assess inequality and equity across social ( S ), ecological ( E ), infrastructural ( I ), and urban ( U ) form determinants ( SEIU ) and environment ( E ), health ( H ), well‐being ( W ), and economy and security ( E ) outcomes ( EHWE ), identifying a universe of >110 SEIU–EHWE data layers (variables) of interest; (3) Provides an illustrative data case study of a US city that synthesizes publicly available sources of the associated SEIU–EHWE data attributes, noting their availability/gaps at fine spatial scales, important to inform social inequality; (4) Discusses analytic methods to quantify inequality and spatial correlates across SEIU determinants and EHWE outcomes; and, (5) Demonstrates several use‐cases of the data framework and companion analytic methods through real‐world applied case studies that inform equity planning in applications ranging from energy sector investments to air pollution and health. The US data case study reveals data availability (covering 41 of the 113 data layers) as well as major gaps associated with EHWE outcomes at fine spatial scales, while the application examples demonstrate practical use. Overall, the SEIU–EHWE data framework provides an anchor for systematically gathering, analyzing, and informing multiple dimensions of inequality and equity in sustainable urban systems.

Systemic Treatment with the Enteric Bacterial Fermentation Product, Propionic Acid, Reduces Acoustic Startle Response Magnitude in Rats in a Dose-Dependent Fashion: Contribution to a Rodent Model of ASD - Corey L. Kamen; Danna L. Zevy; Jordan M. Ward; Indra R. Bishnoi; Martin Kavaliers; Klaus-Peter Ossenkopp (Neurotoxicity Research, 2019)

Exercise intensity effects on total sweat electrolyte losses and regional vs. whole-body sweat [Na+], [Cl−], and [K+] - Lindsay B. Baker; Peter John D. De Chavez; Corey T. Ungaro; Bridget C. Sopeña; Ryan P. Nuccio; Adam J. Reimel; Kelly A. Barnes (European Journal of Applied Physiology, 2019)

A boundary current drives synchronous growth of marine fishes across tropical and temperate latitudes - Joyce J. L. Ong; Adam N. Rountrey; Bryan A. Black; Hoang Minh Nguyen; Peter G. Coulson; Stephen J. Newman; Corey B. Wakefield; Jessica J. Meeuwig; Mark G. Meekan (Global Change Biology, 2018)
Entrainment of growth patterns of multiple species to single climatic drivers can lower ecosystem resilience and increase the risk of species extinction during stressful climatic events. However, predictions of the effects of climate change on the productivity and dynamics of marine fishes are hampered by a lack of historical data on growth patterns. We use otolith biochronologies to show that the strength of a boundary current, modulated by the El Niño‐Southern Oscillation, accounted for almost half of the shared variance in annual growth patterns of five of six species of tropical and temperate marine fishes across 23° of latitude (3000 km) in Western Australia. Stronger flow during La Niña years drove increased growth of five species, whereas weaker flow during El Niño years reduced growth. Our work is the first to link the growth patterns of multiple fishes with a single oceanographic/climate phenomenon at large spatial scales and across multiple climate zones, habitat types, trophic levels and depth ranges. Extreme La Niña and El Niño events are predicted to occur more frequently in the future and these are likely to have implications for these vulnerable ecosystems, such as a limited capacity of the marine taxa to recover from stressful climatic events.

Individual fitness and the effects of a changing climate on the cessation and length of the breeding period using a 34‐year study of a temperate songbird - Corey E. Tarwater; Peter Arcese (Global Change Biology, 2018)
Studies of the phenological responses of animals to climate change typically emphasize the initiation of breeding although climatic effects on the cessation and length of the breeding period may be as or more influential of fitness. We quantified links between climate, the cessation and length of the breeding period, and individual survival and reproduction using a 34‐year study of a resident song sparrow ( Melospiza melodia ) population subject to dramatic variation in climate. We show that the cessation and length of the breeding period varied strongly across years, and predicted female annual fecundity but not survival. Breeding period length was more influential of fecundity than initiation or cessation of breeding alone. Warmer annual temperature and drier winters and summers predicted an earlier cessation of breeding. Population density, the date breeding was initiated, a female's history of breeding success, and the number of breeding attempts initiated previously also predicted the cessation of breeding annually, indicating that climatic, population, and individual factors may interact to affect breeding phenology. Linking climate projections to our model results suggests that females will both initiate and cease breeding earlier in the future; this will have opposite effects on individual reproductive rate because breeding earlier is expected to increase fecundity, whereas ceasing breeding earlier should reduce it. Identifying factors affecting the cessation and length of the breeding period in multiparous species may be essential to predicting individual fitness and population demography. Given a rich history of studies on the initiation of breeding in free‐living species, re‐visiting those data to estimate climatic effects on the cessation and length of breeding should improve our ability to predict the impacts of climate change on multiparous species.

Age and years to death disparately influence reproductive allocation in a short‐lived bird - Corey E. Tarwater; Peter Arcese (Ecology, 2017)
Theory predicts that reproduction will change as individuals near the end of their lives by either increasing reproductive allocation (terminal allocation hypothesis) or decreasing allocation (senescence hypothesis) toward the end of life. Although senescence has received more support, few studies examine how both age and years to death influence late‐life reproduction. We used a 37‐yr study of Song Sparrows ( Melospiza melodia ) to ask how age and years to death influenced reproductive allocation late in life. We observed both senescence and terminal allocation, and that age and years to death interacted to influence individual variation in allocation tactics. In particular, we observed a decline in allocation in older individuals (senescence), but only when comparing individuals with the same number of years to death. Likewise, we observed terminal allocation, but only in young females. Reproductive tactics were most variable in young females, with many exerting high effort but living 1–2 yr, and others exerting low effort annually and living longer. Our results suggest that late‐life reproductive tactics are influenced by both chronological age and years to death, and that short‐ and long‐lived females with differing reproductive tactics exist within this population of Song Sparrows.

Young females pay higher costs of reproduction in a short-lived bird - Corey E. Tarwater; Peter Arcese (Behavioral Ecology and Sociobiology, 2017)

Spheroid culture of LuCaP 136 patient-derived xenograft enables versatile preclinical models of prostate cancer - Maija P. Valta; Hongjuan Zhao; Matthias Saar; Johanna Tuomela; Rosalie Nolley; Johannes Linxweiler; Jouko Sandholm; Jaakko Lehtimäki; Pirkko Härkönen; Ilsa Coleman; Peter S. Nelson; Eva Corey; et al. (Clinical & Experimental Metastasis, 2016)

Different ornaments signal male health and MHC variation in two populations of a warbler - Linda A. Whittingham; Corey R. Freeman‐Gallant; Conor C. Taff; Peter O. Dunn (Molecular Ecology, 2015)
Male traits that signal health and vigour are used by females to choose better quality mates, but in some cases the male trait selected by females differs among populations. Multiple male traits can be maintained through female mate choice if both traits are equally honest indicators of male quality, but tests of this prediction are rare. By choosing males based on such traits, females could gain direct benefits from males (assistance with parental care), but when females choose extra‐pair mates based on these traits, females gain only male sperm, and potentially indirect genetic benefits for their offspring. In common yellowthroats ( Geothylpis trichas ), female choice of extra‐pair mates targets two different plumage ornaments: the black mask in a Wisconsin population and the yellow bib in a New York population. Previously, we found that the black mask in Wisconsin is related to greater major histocompatibility complex ( MHC ) class II variation, which in turn signals better survival and disease resistance. In this study, we examined the signalling function of the yellow bib in New York to test whether it signals the same aspects of male quality as the black mask in Wisconsin. As predicted, we found that the yellow bib in New York is most closely associated with MHC variation, which also signals survival and resistance to blood parasites. Thus, the ornament preferred by females differs between the two populations, but the different ornaments signal similar aspects of male health and genetic quality, specifically information regarding MHC variation and potential indirect genetic benefits to females.

Intermittent aeration affects the bioremediation potential of two red algae cultured in finfish effluent - Scott Caines; Juan A. Manríquez-Hernández; Jim Duston; Peter Corey; David J. Garbary (Journal of Applied Phycology, 2014)

Growth and nutrient uptake by Palmaria palmata integrated with Atlantic halibut in a land-based aquaculture system - Peter Corey; Jang K. Kim; Jim Duston; David J. Garbary (Algae, 2014)

Prostate cancer derived prostatic acid phosphatase promotes an osteoblastic response in the bone microenvironment - Sandy R. Larson; Jessica Chin; Xiaotun Zhang; Lisha G. Brown; Ilsa M. Coleman; Bryce Lakely; Martin Tenniswood; Eva Corey; Peter S. Nelson; Robert L. Vessella; Colm Morrissey (Clinical & Experimental Metastasis, 2014)

Bioremediation potential of Palmaria palmata and Chondrus crispus (Basin Head): effect of nitrate and ammonium ratio as nitrogen source on nutrient removal - Peter Corey; Jang K. Kim; Jim Duston; David J. Garbary; Balakrishnan Prithiviraj (Journal of Applied Phycology, 2013)

Temporal and spatial variation in the distribution of life history phases of Chondrus crispus (Gigartinales, Rhodophyta) - David J. Garbary; Elizabeth Tompkins; Katelyn White; Peter Corey; Jang-K. Kim (Algae, 2011)

Mapped quadrats in sagebrush steppe: long‐term data for analyzing demographic rates and plant–plant interactions - Luke Zachmann; Corey Moffet; Peter Adler (Ecology, 2010)
This historical data set consists of 26 permanent 1‐m 2 quadrats located on sagebrush steppe in eastern Idaho, USA. During most growing seasons from 1923 to 1957, and again in 1973, all individual plants in each quadrat were identified and mapped. This combination of a long time‐series with full spatial resolution allows analyses of demographic processes and intra‐ and interspecific interactions among individual plants. The data provide unique opportunities to test theory about the effect of environmental variation on population and community dynamics and to describe empirical relationships between climate variables and demographic rates. We provide the following data and data formats: (1) the digitized maps in shapefile format; (2) a tabular version of the entire data set (a table with no spatial information except an x,y coordinate for each individual plant record); (3) a species list, containing information on plant growth forms and shapefile geometry type; (4) a record of changes to species names; (5) quadrat information; (6) grazing treatment information; (7) an inventory of the years each quadrat was sampled; (8) monthly precipitation, temperature, and snowfall records; and (9) counts of annuals in the quadrats. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Modifier gene study of meconium ileus in cystic fibrosis: statistical considerations and gene mapping results - Ruslan Dorfman; Weili Li; Lei Sun; Fan Lin; Yongqian Wang; Andrew Sandford; Peter D. Paré; Karen McKay; Hana Kayserova; Tereza Piskackova; Milan Macek; Kamila Czerska; et al. (Human Genetics, 2009)

Differential expression of angiogenesis associated genes in prostate cancer bone, liver and lymph node metastases - Colm Morrissey; Lawrence D. True; Martine P. Roudier; Ilsa M. Coleman; Sarah Hawley; Peter S. Nelson; Roger Coleman; Ya-Chun Wang; Eva Corey; Paul H. Lange; Celestia S. Higano; Robert L. Vessella (Clinical & Experimental Metastasis, 2008)

Managing an Endangered Asian Bovid in an Australian National Park: The Role and Limitations of Ecological-Economic Models in Decision-Making - Barry W. Brook; David M. J. S. Bowman; Corey J. A. Bradshaw; Bruce M. Campbell; Peter J. Whitehead (Environmental Management, 2006)

The cystic fibrosis transmembrane conductance regulator gene and ion channel function in patients with idiopathic pancreatitis - Michele D. Bishop; Steven D. Freedman; Julian Zielenski; Najma Ahmed; Annie Dupuis; Sheelagh Martin; Lynda Ellis; Julie Shea; Isobel Hopper; Mary Corey; Paul Kortan; Gregory Haber; et al. (Human Genetics, 2005)